Effects of unprotected choline chloride on microbial fermentation in a dual-flow continuous culture depend on dietary neutral detergent fiber concentration - Arce Cordero, José Alberto (2021)
La Universidad de Costa Rica apoyó el programa de doctorado de José Alberto Arce Cordero